Chronic Thromboembolic Pulmonary Hypertension, Pregnancy, and a Pulmonary Endarterectomy: A Rare Challenge. (September 2016) - Rosenzweig, Erika B.; Biscotti, Mauer; Cleary, Kirsten; Smiley, Richard; Bacchetta, Matthew D.
It is well described that patients with group 1 forms of pulmonary arterial hypertension have a high risk of mortality during pregnancy and in the early postpartum period. However, to the authors' knowledge, the diagnosis and management of group 4 pulmonary hypertension due to chronic thromboembolic pulmonary hypertension (CTEPH) during pregnancy with early postpartum pulmonary endarterectomy (PEA) has not been previously reported. We report the case of a 28-year-old woman who received a diagnosis of CTEPH during her pregnancy, was managed as an inpatient by a multidisciplinary team throughout the pregnancy and early postpartum period, and underwent PEA 6 weeks after delivery. While the management of acute pulmonary embolus in pregnancy is well described, this unique case of CTEPH diagnosed during pregnancy illustrates several challenging management issues.